The Influence of Women's Development and Empowerment on Inclusive Economic Growth - Alya Mafida Amalia; Farida Rahmawati; Inayati Nuraini Dwi Putri (PT. EQUATOR SINAR AKADEMIA, 2023)
Inclusive Economic Growth in Indonesia is formed through aspects of economic growth, inequality, and access to opportunities. Equitable development and empowerment that is focused on women provide access to opportunities in realizing inclusive economic growth. This research was conducted with the aim of knowing the effect of women's development and empowerment on inclusive economic growth in provinces in Indonesia in 2012-2021. This research uses secondary data, uses a quantitative approach with the method of panel data regression analysis with a fixed effect model. The regression results found that women's development variables through the gender development index indicator showed that women's life expectancy had a significant negative effect, while the average length of schooling for women and women's per capita expenditure had a significant positive effect. The variable of women's empowerment through the gender empowerment index indicator found that women's involvement did not have a significant effect on inclusive economic growth and the variables of women as professionals and contribution of women's income had a significant positive effect on inclusive economic growth in 2012-2021. Four of the six variables showed significant positive results. This indicates that the development and empowerment of women can improve welfare which affects growth. There needs to be a policy formulation on women that must be carried out by each region to help fulfill women's rights and reduce gender discrimination.